2020
DOI: 10.1136/medethics-2020-106639
|View full text |Cite
|
Sign up to set email alerts
|

Frauds in scientific research and how to possibly overcome them

Abstract: Frauds and misconduct have been common in the history of science. Recent events connected to the COVID-19 pandemic have highlighted how the risks and consequences of this are no longer acceptable. Two papers, addressing the treatment of COVID-19, have been published in two of the most prestigious medical journals; the authors declared to have analysed electronic health records from a private corporation, which apparently collected data of tens of thousands of patients, coming from hundreds of hospitals. Both p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 16 publications
0
27
0
1
Order By: Relevance
“…This was the case in the early years of human stem cell research, later in the field of micro-and other non-coding RNAs, and in general in every research field with a fancy prefix, like currently nano-. The still ongoing the COVID-19 crisis already yielded many publications in this field, which on several occasions resulted in retractions and scandals (Boetto et al 2020).…”
Section: How To Detect "Figure Issues" Yourself Within 1 H?mentioning
confidence: 99%
“…This was the case in the early years of human stem cell research, later in the field of micro-and other non-coding RNAs, and in general in every research field with a fancy prefix, like currently nano-. The still ongoing the COVID-19 crisis already yielded many publications in this field, which on several occasions resulted in retractions and scandals (Boetto et al 2020).…”
Section: How To Detect "Figure Issues" Yourself Within 1 H?mentioning
confidence: 99%
“…53 The scandal exposed the flaws in today's peer review and scientific data use processes, requiring mechanisms to prevent manipulation and promote transparency. 54 Open science initiatives can be facilitated through distributed ledger technologies, which can be encouraged by journals by providing a 'license of reliability' to those that enable transparent data review, as seen with blockchain. 54 55 Further opportunities may present for improving the transparency and validity of systematic reviews and meta-analyses, which are commonly at the basis of scientific and medical guidelines in addition to expert panels.…”
Section: Research Open Science and Misinformationmentioning
confidence: 99%
“…In the case of the two Mehra et al retractions, data originated from a data analytics company, Surgisphere, whose website has since disappeared. Data of thousands of patients across six continents were ruled as invalid and unsafe because it was unverifiable (21) . Potential risks of using hydroxychloroquine or chloroquine as a treatment for COVID-19 (10) , advice that was used by the World Health Organization (WHO) and that was also based on the Surgisphere dataset, was also invalidated (21) .…”
Section: Surgisphere Reliability Of Public Data Sources and Unfair Citationsmentioning
confidence: 99%
“…Data of thousands of patients across six continents were ruled as invalid and unsafe because it was unverifiable (21) . Potential risks of using hydroxychloroquine or chloroquine as a treatment for COVID-19 (10) , advice that was used by the World Health Organization (WHO) and that was also based on the Surgisphere dataset, was also invalidated (21) . Despite this, a Google Scholar on March 1, 2021 search revealed that the two retracted papers continue to be heavily cited, 971 and 804 times, respectively (10,11) , although it is very important to appreciate which citations are valid, i.e., based on a critique of the retracted papers, and to differentiate such citations from invalid citations, which are based on the assumption that the findings of those studies continue to be valid.…”
Section: Surgisphere Reliability Of Public Data Sources and Unfair Citationsmentioning
confidence: 99%